A multi-disciplinary team approach to pediatric malignant mandibular tumors. (May 2023) - Hintze, Justin M.; Afshar, Salim; Taghinia, Amir; Labow, Brian; Green, Mark; Robson, Caroline D.; Marcus, Karen; Mack, Jennifer; Perez-Atayde, Antonio; Rahbar, Reza
Abstract: Objective: Mandibular tumors in the pediatric population are rare. These malignancies are variable in their histology, and combined with their rarity, has made it difficult to describe their clinical course, and treatment guidelines. The aim of this paper is to describe the experience of Boston Children's Hospital, a pediatric tertiary referral center, with treating malignant mandibular malignancies, as well as provide multi-disciplinary team approach in managing this clinical entity. Methods: A retrospective search was performed for mandibular malignancies in pediatric patients between 1995 and 2020 via the pathological database at Boston Children's Hospital. Only patients with malignant solid mandibular neoplasms were included, leaving 15 patients for final analysis. Results: The median age at presentation was 10.1 ± 10.3 years. Nine of 15 patients (60%) presented with jaw mass which was the most common clinical presentation. The most commonly identified histological diagnosis was rhabdomayosarcoma and osteosarcoma (n = 4, 26% each). A mandibulectomy was performed in 12 (80%) cases. Reconstruction of the mandible was performed using a fibular free flap in 6 (40%) cases, and a plate in 3 (20%) cases. Mean follow-up was 4.6 ± 4.9 years. Conclusion: Malignant tumors most commonly present with a jaw mass, however asymptomatic and incidental presentations follow closely and pathologies can vary greatly. Surgical resection and reconstruction is often indicated, multidisciplinary tumor board review is required to determine when children are best treated with neo-/adjuvant treatment with chemo- and radiotherapy.